High temperature oxidation pre-treatment of textured c-Si wafers passivated by a-Si:H. (July 2019) - Limodio, G.; D'Herouville, G.; Mazzarella, L.; Zhao, Y.; Yang, G.; Isabella, O.; Zeman, M.
Abstract: This work shows an alternative surface cleaning method for c-Si wafers to replace the standard chemical procedures as RCA or HNO3 which involve hazardous chemicals or unstable processes. The method consists in a high-temperature oxidation treatment (HTO) performed in a classical tube furnace that incorporates organic and metal particles present on the c-Si surfaces in the growing SiO2 layer. The result is as a reliable pre-treatment method for obtaining less defective c-Si surfaces ready for solar cell fabrication after SiO2 removal. To test the surface passivation quality obtained with our alternative cleaning method, we grow amorphous silicon (a-Si:H) layers by plasma enhanced chemical vapor deposition on both sides of the c-Si wafer and systematically compare the effective carrier lifetime (τeff ) and implied VOC (iVoc ) to the wafer treated with the standard cleaning in our laboratory. We optimize HTO treatment time reaching τeff of ∼6 ms and iVoc of 721 mV for the best sample. We ascribe the improved passivation quality using HTO to two concurrent factors. Firstly, the encapsulation of defects into SiO2 layer that is then etched prior a-Si:H deposition and secondly, to modification of the pyramids' morphology that facilitates the surface passivation. SEM pictures and reflection measurements support the latter hypothesis.